The Necessity of Transitioning from Traditional Class Management to Student Autonomous management in Chinese Basic Education - Lu, Chang (Science Insights Education Frontiers, 2025)
Class management is a basic component of school governance in basic education. Traditional class management in China has overemphasized teacher control, discipline, and order, restricting students’ all-round development. In the context of intensified educational reforms, there is a need for transitioning to student autonomous management, a more student-centered class management style. This article gives a brief overview of the evolution of class management in modern China, expounds on the necessity of introducing student autonomous management as well as its chief features, and proposes pathways for its implementation, with the view to providing insights for ongoing educational reform in China.